The first experimental research on the pathogenicity of Arcobacter butzleri in zebrafish - Acik, Mehmet Nuri; Yuksel, Hayati; Ulucan, Aykut; Cetinkaya, Burhan (Elsevier, 2016)
This experimental study was conducted to investigate the pathogenicity and histopathology of Arcobacter butzleri in zebrafish model organism. Firstly, mean infective dose (ID50) of A. butzleri was calculated in zebrafish as 1.3 x 10(8) CFU/mL and 1 x 10(5) CFU/mL by immersion and intraperitoneal injection, respectively. For histopathological trials, the ID50 of A. butzleri were given to zebrafish by both immersion and intraperitoneal routes and then, clinical and pathological findings were evaluated on days 1, 3, 5, 7 and 21 of the experiment. During the experimental period, no clinical signs or gross lesions of disease were observed in the zebrafish groups infected with the ID50 of A. butzleri by either method. In the histopathological examination, acute inflammation characterized by neutrophil and plasma cells and local necrosis or congestion were determined in liver, kidney, spleen, gaster and other visceral organs. In addition peritonitis, leukocyte infiltration, villous atrophy and septicemia were observed in the experimental groups. Neither gross nor microscopic lesions were detected in the control groups. This study presented the first report of experimental A. butzleri infection in wild zebrafish. In the light of the findings obtained here, it was concluded that zebrafish could be used as a model organism to investigate pathogenicity and histopathology of arcobacters. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Arcobacter butzleri; Zebrafish; ID50; Histopathology